ON THE HISTORICAL DEVELOPMENT OF PHONETICS OF THE TURKIC LANGUAGES - Nurmanov F.I. (Scholar Express Journal, 2021)
The article describes the specific linguistic features of Turkic languages, in particular, the theoretical views of Eastern scientists on the phonetics section, their place and significance in Turkic linguistics
Keywords: phonetics; sound; letter; phoneme